Reviews DVD/Blu-ray. Issue 3 (1st September 2015) - Guglielmi, Philip; Hang, Yeng; Marsellus, Mynt; Berndt, Victoria; Grant, Matthew; Marsellus, Mynt; McBain, Sarah; Miller, Aaron; Bahr, Kevin; Beaney, Rachel; Getz, Adam; Blankenship, Paige
Three Views of An Autumn Afternoon An Autumn Afternoon (1962) Japan Director Yasujiro Ozu Runtime 113 minutes Blu-ray USA, 2015 Produced and Distributed by The Criterion Collection (region 1)All That Heaven Allows (1955) USA Director Douglas Sirk Runtime 89 minutes Dual-Format Edition Blu-ray/DVD USA, 2014 Produced and Distributed by The Criterion Collection (region 1)Make Way for Tomorrow (1937) USA Director Leo McCarey Runtime 92 minutes Blu-ray USA, 2015 Produced and Distributed by The Criterion Collection (region A/1)Pickpocket (1959) France Director Robert Bresson Runtime 76 minutes Dual-Format Edition 1 Blu-ray/1 DVD USA, 2014 Produced and Distributed by The Criterion Collection (region 1)Farewell Shire, Hello Virtual World: CGI in The Hobbit The Hobbit: An Unexpected Journey (Extended Edition) (2012) Director Peter Jackson Runtime 182 minutes DVD USA, 2013 Produced and Distributed by Warner Bros. Pictures Home Entertainment Company (region 1)Breaking the Waves in 1 Frame Breaking the Waves (1996) Denmark Director Lars von Trier Runtime 159 minutes Dual Format Blu-ray/DVD USA, 2014 Produced and Distributed by The Criterion Collection (region A/1)